Serum Free Light Chains in Neoplastic Monoclonal Gammopathies: Relative Underproduction and Underdetection of Free Lambda Light Chains, as Compared to Kappa Light Chains, in Patients With Neoplastic Monoclonal Gammopathies. (21st September 2018) - Lee, Won; Singh, Gurmukh
Abstract: Background: Serum free light chain (SFLC) assay has been promoted for diagnosing, determining the prognosis, and monitoring of monoclonal gammopathies. Currently, serum protein electrophoresis (SPEP) and serum protein immunofixation electrophoresis (SIFE) are commonly used as screening tests, and the findings of SIFE are the gold standard for identification of monoclonal immunoglobulins according to the International Myeloma Workshop Consensus Panel 3. Urine protein electrophoresis (UPEP) and urine protein immunofixation electrophoresis (UIFE) are also recommended. Immunoglobulin light chains are generally produced in excess of heavy chains. In patients with monoclonal gammopathy, κ/λ ratio is abnormal less frequently with lambda chain lesions. This study was undertaken to ascertain if the high false-negative rate for SFLC results for lambda chain lesions was due to underdetection of lambda light chains or underproduction of lambda light chains or both. Methods: Data from 482 patients comprising 2, 448 observations were reviewed retrospectively from January 2010 through September 2017 in a 480-bed tertiary medical center. Of these, 249 observations corresponding to 175 patients with neoplastic monoclonal gammopathies (NMGs), including monoclonal gammopathy of undetermined significance, smoldering multiple myeloma, or multiple myeloma, were examined. SPEP, SIFE, UPEP, and UIFE were carried using a Helena (Beaumont, TX) SPIFE 3000. SFLC assay was done by using reagent kits from The Binding Site, (Birmingham, UK) on an Optilite instrument. Comparison of results of different groups was done by the chi-square test. Results: UIFE results were divided into three categories: UIFE0, when no monoclonal immunoglobulin (Ig) or free light chains were detected; UIFE1, when monoclonal free light chains were detected with or without intact monoclonal Ig; and UIFE2, when only intact monoclonal Ig was detected. κ/λ ratios were abnormal more often in kappa chain lesions with χ 2 (10.4–12.9) and P value (0.0003–0.0006). κ/λ ratios were normal in about 25% of UIFE1 category of patients (10 out of 31) with lambda chain lesions in whom free homogeneous lambda light chains were detectable in urine. None of the patients with kappa chain lesions and UIFE positive for monoclonal kappa light chains showed a normal κ/λ ratio. An illustrative case is identified in which a patient with biclonal gammopathy with a dominant IgG λ lesion suggests underproduction of free lambda light chains, in some instances. Conclusions: The 30% false-negative κ/λ ratio in patients with lambda chain monoclonal gammopathy is due to underdetection of lambda light chains, by the Binding Site assay, in about 25% of the patients. In the remaining 5% of patients, the false-negative κ/λ ratio is estimated to be due to underproduction of excess free lambda light chains. The results question the medical necessity and clinical usefulness of the SFLC assay as well as arguing for the greater use of UPEP/UIFE.